How Much Does Physical Infrastructure Contribute to Economic Growth? An Empirical Analysis - Timilsina, Govinda; Stern, David I.; Das, Debasish K. (World Bank, Washington, DC, 2021)
Existing literature on the relationship between infrastructure and economic growth is inconclusive. This study evaluates the contributions to economic growth of three main categories of infrastructure—transport, electricity, and telecommunications—using data from 87 countries over 1992–2017. Compared with existing studies, this study uses more recent data, includes new types of infrastructure such as mobile phones, and provides separate estimates for developing and developed countries. The pooled mean group estimator, which tests for the weak exogeneity of the infrastructure variables, is employed. The key finding of the study is that an increase in infrastructure, especially electricity generation capacity and telecommunications, has significant positive effects on gross domestic product. Infrastructure has a larger effect in more recent years (1992–2017) than in earlier years (1970–1991), and the effects of infrastructure are higher in developing economies than in industrialized economies.